Water hammer with non-equilibrium gas release. (August 2018) - Ivljanin, Bojan; Stevanovic, Vladimir D.; Gajic, Aleksandar
Abstract: Water hammer transient with gaseous cavitation in a pipe shows that the amplitude of the first pressure surge, caused by the closure of the fast valve, is approximate to the Joukowsky pressure rise in liquid, while subsequent pressure surges are strongly influenced by the presence of air in the mixture with liquid water. These conditions are described and numerically simulated with the homogeneous two-phase flow model and a non-equilibrium model of air mass transfer between dispersed air bubbles and continuous liquid water. It is found that the generation of air bubbles is intensive when the rarefaction wave decreases pressure below the pressure of gas saturation in water for the first time after the Joukowsky pressure peak, while, later on, the mass transfer rate, due to air degassing and absorption, is much smaller. A numerically predicted pressure transient is validated by the comparison with available measured data, and an excellent agreement is achieved. Highlights: New non-equilibrium model of gaseous cavitation in water hammer transient. Homogeneous model governing equations for both single-phase and two-phase flows. Accurate numerical prediction of water hammer with gaseous cavitation. Intensive degassing at the first pressure drop below the pressure of air saturation in water. Sensitivity of pressure surges on various process parameters is evaluated.